UBR5 Significantly Correlates with Osteosarcomas Prognosis and Immune Exhaustion Characteristic in the Tumor Microenvironment - lin, Hai; Zhang, Liyan; Liu, Bin; Cui, Guopeng (Current Cancer Drug Targets, 2024)
Background: Ubiquitin ligases (E3s) play an important role in multiple cancers. Methods: The open-accessed expression profile and clinical information was downloaded from the TARGET database. The analysis was performed using R software. Results: In this study, we comprehensively investigated the role of E3s in osteosarcomas (OS). We found that among all these E3s, UBR5 is a risk factor for OS. Considering that UBR5 has not been reported in previous studies focused on OS, we selected it for further analysis. Interestingly, we found that UBR5 had no significant effect on immune cell infiltration but a remarkable effect on immune function. Moreover, we divided the patients into “immune activation” and “immune exhaustion” types. KM survival curves indicated that the patients in the “immune exhaustion” types had a worse survival performance. Further, we identified the molecules involved in immune function and significantly correlated with UBR5. The biological enrichment analysis and prognosis model were then conducted based on these genes. Results indicated that the patients in the high-risk group had a worse survival performance, and underlying biological differences between high and low-risk patients were also explored. Ultimately, the effect pattern of UBR5 in pan-cancer was also explored. Conclusion: In summary, our study comprehensively explored the role of UBR5 in OS, as well as its effect on the immune microenvironment, which might be an underlying therapy target.
Keywords: UBR5